Designing Risk Mitigation Strategies Using Enterprise Risk Management (ERM) Based on COSO ERM and House Of Risk (HOR) Models - Tsabitah, Aliva; Chumaidiyah, Endang; Suhendra, Agus Ahmad (Journal of Ecohumanism, 2025)
Maritime transportation, as a crucial means of global connectivity, is inherently exposed to various risks. PT. XYZ, a company in this sector, faces significant operational and strategic risks. However, the absence of a dedicated risk management division or a structured mitigation strategy highlights a critical gap in its ability to address these vulnerabilities effectively. This study aims to develop a comprehensive risk mitigation framework that empowers the company to take early preventive actions and strengthen its resilience against potential risks. The research employs the COSO ERM 2017 framework, integrated with the House of Risk (HOR) approach, combining qualitative and quantitative methodologies for comprehensive risk assessment. The findings identify 29 distinct risk events and 42 associated risk agents. By prioritizing these risks using the HOR approach, the study formulates 16 actionable risk mitigation strategies, tailored to address the most pressing threats. The proposed framework emphasizes proactive measures and continuous monitoring to ensure sustainable risk management practices. Recommendations include institutionalizing a dedicated risk management division and embedding the framework into daily operations to foster a risk-aware culture. This study provides a practical and structured approach to risk mitigation, offering valuable insights for PT. XYZ and the broader maritime industry to navigate uncertainties effectively and ensure long-term operational stability.